The Relationship Between Trust in Spouse and Interpersonal Conflict in Husband Who Undergoes Long Distance Marriage in Makassar City - Pawiloi, Andi Andini Thasya; Firdaus, Faradillah; ., Irdianti (Polteknik Ilmu Pemasyarakatan, 2024)
Although long-distance marriage has become a common phenomenon in today's era, interpersonal conflict issues often arise within it, one of which is trust in the partner. This study aims to determine the relationship between Trust in the Partner and Interpersonal Conflict among Husbands in Long-Distance Marriages in Makassar City. This research employs a quantitative approach. The population in this study consists of married couples currently undergoing long-distance marriages in Makassar City, with a sampling technique using snowball sampling technique with 200 respondents calculated using Hair's formula. The results of this study indicate a significant negative relationship between trust in the partner and interpersonal conflict among husbands in long-distance marriages in Makassar City (r= -0.622, p=0.000). The higher the trust in the partner, the lower the interpersonal conflict among husbands, conversely, the lower the trust in the partner, the higher the interpersonal conflict among husbands. The findings of this study imply that husbands in long-distance marriages need to enhance trust in their partners to reduce interpersonal conflicts in the relationship.